Market Feasibility Analysis and Willingness to Pay for Halal Products Based on Digital Traceability - Sabrina Kharisma Suri; Sri Hardiyanti; Fatkhur Rokhman (Journal of Industrial Engineering and Halal Industries, 2026)
A digital traceability system is required to improve transparency, security, and consumer trust in the halal goods sector as the halal business grows and becomes increasingly connected to digital technology. The deployment of a computerised tracking system is thought to provide consumers with more precise information on the source of raw materials, manufacturing procedures, and halal product distribution. This study's objective is to investigate customer willingness to pay as well as commercial viability for halal products based on digital traceability. The study employs a descriptive design and a quantitative methodology. Purposive sampling was used to gather primary data by distributing questionnaires to Muslim customers who had access to digital technologies and had bought halal goods. Multiple linear regression will be used in the data analysis to examine how market viability and digital traceability factors affect willingness to pay. This will be preceded by traditional assumption testing to make sure the study model is appropriate. This study is anticipated to make a scholarly addition to the advancement of technology-based halal economy studies and to be taken into account by business actors when developing development strategies for halal products based on a digital traceability system.